Zadovoljstvo učiteljev z delovno situacijo - Kapun, Sanja; Kešina, Karmen; Čagran, Branka (Revija za elementarno izobraževanje, 2009)
Teachers’ satisfaction with their work situation. In the article we discuss teacher work-satisfaction as a factor in the qualitative educational process. In the empirical research we established levels of satisfaction through the perspective of material factors, personal growth factors, social factors and factors of autonomous-creative work. The results show the existence of differences in the teachers’ answers regarding the permanency of employment and work experience: teachers who do not have permanent positions are more satisfied with their work situation; the same is true for teachers with more work experience.